An Improved Transformation System for Cowpea (Vigna unguiculata L. Walp) via Sonication and a Kanamycin-Geneticin Selection Regime - Bett, Bosibori; Gollasch, Stephanie; Moore, Andy; Harding, Robert; Higgins, Thomas J. V. (Frontiers in Plant Science, 2019)
An improved cowpea transformation method utilizing Agrobacterium-mediated gene delivery to explants derived from the cotyledonary nodes of imbibed cowpea seed is described. The explants were regenerated following a sonication procedure and a stringent selection comprising alternating regimes of kanamycin and geneticin. The method was reproducible and led to the recovery of independent fertile transgenic plants in the greenhouse at a level of about one per cent of starting explants. A transgene encoding an insecticidal protein from Bacillus thuringiensis was used to demonstrate the efficacy of the system.